Integrated Education and Screening Program: Preventing Frailty Risk and Promoting Elderly Health - Yakobus Siswandi; Eva Berthy Tallutondok; Martha Ocataria; Erivita Sakti; Shinta Marina J. P. Sihaloho (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Aging increases the risk of frailty and metabolic disorders among older adults, which may reduce physical, mental, and social functioning and accelerate disability. This Community Service Program (Pengabdian kepada Masyarakat/PkM) at the Toraja Church Congregation in Tangerang aimed to improve older adults’ awareness and knowledge regarding frailty prevention through health education and integrated health screening. In addition, this program also aimed to identify the health conditions of older adults, including anthropometric status, metabolic conditions, blood pressure, physical strength, and frailty levels as part of early detection and prevention of frailty progression. This activity is expected to support the improvement of quality of life and independence among older adults as a contribution to achieving the Sustainable Development Goals (SDGs), particularly SDG 3 on good health and well-being. The methods included screening for fasting blood glucose, cholesterol, uric acid, vital signs, body mass index (BMI), muscle mass, mid-upper arm circumference (MUAC), calf circumference, handgrip strength, and frailty assessment using the Clinical Frailty Scale, followed by education through modules, presentations, and learning videos. The results among 16 older adults showed that the majority were aged ≥60 years (62.5%), male (62.5%), and had higher education levels (62.5%). Anthropometric conditions showed that 31.3% were overweight and 68.8% were obese; 87.5% had normal muscle mass, while 12.5% experienced decreased muscle mass. Metabolic screening showed abnormal fasting blood glucose (56.3%), high uric acid levels (68.8%), and high cholesterol levels (56.3%). High systolic blood pressure was found in 56.3% of participants, while the majority had normal pulse rates (87.5%). Frailty assessment showed that 62.5% were categorized as pre-frail, 25% as frail, and 12.5% as robust. Educational evaluation results demonstrated an increase in the average knowledge score from 75.65 to 81.36. The conclusion of this Community Service Program at the Toraja Church Congregation in Tangerang showed that most older adults were in the pre-frailty and frailty categories, accompanied by a high prevalence of obesity and metabolic disorders such as hyperglycemia, hyperuricemia, hypercholesterolemia, and hypertension. The implementation of integrated health screening combined with health education was proven to improve older adults’ knowledge regarding frailty prevention and the importance of maintaining a healthy lifestyle. Therefore, continuous screening and education programs are needed as efforts for early detection, prevention of frailty progression, improvement of quality of life, and maintenance of independence among older adults. Older adults are also encouraged to adopt healthy lifestyles through balanced nutrition, physical activity according to their abilities, and regular monitoring of metabolic conditions with support from families, communities, and cross-sector collaboration. Churches are recommended to routinely organize community-based health screening and educational programs for older adults and collaborate with healthcare professionals in monitoring the health conditions of older adults. Furthermore, future Community Service Programs are expected to involve a larger number of participants and develop sustainable intervention programs to support frailty prevention and improve the quality of life of older adults. Keywords: Education, Screening, Frailty, Health, Older Adults.